COMPATIBILITY AMONG WORK ASSOCIATES IN ISOLATED GROUPS - Nelson, Paul D. (1964)
In the present study an attempt was made to identify correlates of work partner compatibility among 14 three- to sixman work groups located in isolated Antarctic stations. Using demographic and self description data to construct group composition variables and sociometric data to derive compatibility criterion measures, work group homogeneity on age was significantly (p < .01) related to work group compatibility. An additional finding of significance (p < .05) was that a low level of compatibility existed among work associates who were equally high in their need to be interpersonally prominent as through leadership status. A general trend in the study was for group composition variables to be more related to compatibility during the winter than during the summer months, the time period of greatest confinement and isolation from the outside world.